Development of Android-based Rental System for Mountaineering Equipment - Elias, Mohammed Nawfal Abdulrahman; Fikri Ahmad Taufiqulhakim; Umi Najiah (Journal of Methodical Computing and Communications, 2025)
The proliferation of mobile commerce has not uniformly addressed the needs of specialized, high-stakes recreational activities. Mountaineering, for instance, presents unique logistical and safety challenges that generic rental platforms fail to accommodate, creating a distinct research gap in domain-specific usability and system design. This study investigates the efficacy of applying a user-centered design (UCD) and Agile development framework to create a specialized mobile rental system tailored for the mountaineering community. The research aimed to determine the critical success factors for designing such a niche application and to evaluate the suitability of an iterative development model in this context. Adopting a constructive research approach, a mobile application for Android was developed as the primary artifact to explore the research problem. The Agile methodology guided the iterative development, while a mixed-methods evaluation, including observational analysis and user usability surveys, provided empirical data. The findings demonstrate that the synthesis of Agile and UCD principles is highly effective, leading to a measurable 2-4% enhancement in key usability metrics across development cycles. The final artifact was validated by target users, depending on the feedback indicating a positive reception to the app's design and functionality — affirming its intuitive design and effectiveness in addressing their specific needs. This thesis contributes a validated model for developing mobile applications in niche recreational markets, offering insights into the critical interplay between domain-specific requirements and software development methodologies. The results confirm that for high-stakes user groups, a tailored design process is paramount and provides a framework for future research in similar specialized domains.